Lower and upper bound intercept probability analysis in amplifier-and-forward time switching relaying half-duplex with impact the eavesdropper - Phu Tran Tin; Van-Duc Phan; Tan N. Nguyen; Nguyen Thai Bao; Nguyen Ngoc Diem; Nguyen Duc Thinh; Minh Tran (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
In this paper, we proposed and investigated the amplifier-and-forward (AF) time switching relaying half-duplex with impact the eavesdropper. In this system model, the source (S) and the destination (D) communicate with each other via a helping of the relay (R) in the presence of the eavesdropper (E). The R harvests energy from the S and uses this energy for information transferring to the D. For deriving the system performance, the lower and upper bound system intercept probability (IP) is proposed and demonstrated. Furthermore, the Monte Carlo simulation is provided to justify the correctness of the mathematical, analytical expression of the lower and upper bound IP. The results show that the analytical and the simulation curves are the same in connection with the primary system parameters.